“ERB’S PALSY; THERE IS A NEED TO IMPROVE SURGICAL INTERVENTION IN PAKISTAN CURRENT ORTHOPEDIC PRACTICE - Farjad Afzal; Sidra Manzoor (Journal of University Medical & Dental College, 2017)
Abstract: Restoring external rotation is real challenge in patient with erb’s palsy. Early conservative treatment responds well to reduce disability, but there is a need to treat residual disability in patients with erb’s palsy with surgical interventions. Erb’s palsy has been remaining a challenging condition and recovery is slow, that’s why there should be some palliative procedures like tendon transfer to prevent further dysfunctioning and disability. Combine loss of active elevation and shoulder external rotation (CLEER) is also seen in many patients due to absence of both teres minor and infraspinatus muscles. Currently there are limited services in Pakistan for patient with erb’s palsy to restore external rotations. External rotation plays a major role in activity of daily life and we can minimize the disability in these children if there is facility and innovation in the field of orthopedic surgical intervention in restoration of external rotation and residual disability.